Metodologia badań przekładów Bhagawadgity - Łozowska, Alicja (Gajt Wydawnictwo 1991 s.c., 2018)
This paper summarizes selected approaches to the translation of the Bhagavadgita. At the beginning some general trends in the translation theory are presented and the Bhagavadgita’s translation is compared to the translation of the Bible, highlighting the difficulties in this process, pointed out by E. Nida. Then specific issues concerning the Bhagavadgita’s translation, like the ways of rendering the philosophical terms, the nicknames of the heroes, stylistics, foreignization etc. are analyzed. This part also includes a concise commentary on the reception of Bhagavadgita and its different interpretations’ problems. In the last part the main issues in the process of translating Bhagavadgita, the questions, that every translator of Bhagavadgita has to answer, are summed up.
Keywords: Bhagavadgītā